2018
DOI: 10.2174/1875399x01811010026
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Drowning Rescue Methods with the Rescuer in Cinema

Abstract: Objective: The use of various rescue methods for coping with drowning as a subject of research is scarce. Method: With a chi-square statistical analysis in a criterion/convenient sample of film scenes (n=430), it was aimed to reveal how the various rescue methods relate to the rescuer and other related sub-variables. Results confirm that cinematography indeed passes several right and wrong hidden messages to their vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Other studies have also suggested that waving and shouting for help does not occur during life-threatening drowning events. The loss of buoyancy during exhalation of air while screaming, and stopping supportive arm movements while raising one or both arms, both impede swimming and floating [ 1 , 6 , 17 , 18 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also suggested that waving and shouting for help does not occur during life-threatening drowning events. The loss of buoyancy during exhalation of air while screaming, and stopping supportive arm movements while raising one or both arms, both impede swimming and floating [ 1 , 6 , 17 , 18 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For many years it has been assumed that a person in the water will scream and wave for help when drowning. This is shaped and reinforced by popular lay-media depictions of drowning [ 6 , 7 ]. Pia [ 8 , 9 ] studied real-situation film footage to form the basis for the “Instinctive Drowning Response” (IDR) theory (eyes fixed to shore, horizontal arm movements just underwater).…”
Section: Introductionmentioning
confidence: 99%